2015
DOI: 10.1016/j.eats.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Treatment of Intraosseous Ganglion Cyst of the Lunate Bone

Abstract: Intraosseous ganglion cysts are rare causes of wrist pain. Surgical treatment of this pathologic condition yields good results and a low recurrence rate. The main complications are joint stiffness and vascular disturbances of the lunate bone. Wrist arthroscopy is a surgical technique that reduces the intra-articular operative area and therefore minimizes postoperative stiffness. This article describes an arthroscopic technique used for lunate intraosseous cyst resection associated with an autologous bone graft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
(7 reference statements)
1
8
0
Order By: Relevance
“…Intraosseous ganglia cysts of the lunate are relatively rare but nonetheless represent a cause of chronic wrist pain, stiffness, or loss of strength. 6 This etiology must be well known not to miss the diagnosis, which is rendered quite easily through simple radiological examination such as plain radiography, MRI, or CT. 12,13 Although most ganglia are often asymptomatic, 7 complications such as lunate wall perforation or fracture, and even secondary flexor tendon injury, 14 can occur and be responsible for a mild to severe handicap of the wrist. 2 Intraosseous ganglia can occur or coexist in other carpal bones, usually scaphoid, capitate, and triquetrum; multiple locations are not rare.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Intraosseous ganglia cysts of the lunate are relatively rare but nonetheless represent a cause of chronic wrist pain, stiffness, or loss of strength. 6 This etiology must be well known not to miss the diagnosis, which is rendered quite easily through simple radiological examination such as plain radiography, MRI, or CT. 12,13 Although most ganglia are often asymptomatic, 7 complications such as lunate wall perforation or fracture, and even secondary flexor tendon injury, 14 can occur and be responsible for a mild to severe handicap of the wrist. 2 Intraosseous ganglia can occur or coexist in other carpal bones, usually scaphoid, capitate, and triquetrum; multiple locations are not rare.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,11,[17][18][19] Several arthroscopic techniques have been reported for ILBG approach and treatment. Ashwood and Bain 11 and Bain et al 6 proposed direct drilling of the lunate, either dorsal or volar, under fluoroscopic control (respectively 8 and 10 cases); Bhatia 18 suggested a similar direct "cystoscopy" through cartilage drilling (1 case), along with Cerlier et al, 7 who also performed direct transosseous approach on the articular side of the lunate, the location of the cyst beforehand specified on CT (4 cases). Rimokh et al 17 recently reported a comparable method (7 cases).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This minimally invasive approach irritates signi cantly less soft tissue; thus, the capsules and ligaments remain intact, reducing the risk of arthro brosis and damage to the vascular system of the carpal bones that might possibly lead to open exposure. [7,15,19] Using an arthroscope, a complete and clear view of the joint could be achieved, subsequently treating the intra-articular lesions. Furthermore, concomitant morbidities such as extraosseous cysts and intercarpal joint instability can also be treated arthroscopically with a better esthetic result.…”
Section: Discussionmentioning
confidence: 99%